Synthesis characterisation and chemistry of N-alkyl-and N,N-dialkyl-N'-acylthiourea platinum(II) and palladium(II) complexes - Wang, Yali (Department of Chemistry, 2016)
N-(n-butyl)-N-methyl-N'-benzoylthiourea and N-(n-butyl)-N-methyl-N'-naphthoylthiourea (HL) have been synthesised and characterised. These ligands react with K2PtCl4 to yield neutral square planar cis- [Pt(L-O,S)2] complexes. These complexes exist as mixture of EE, EZ and ZZ isomers.